2005
DOI: 10.1007/s00134-005-2679-0
|View full text |Cite
|
Sign up to set email alerts
|

Successful long-term program for controlling methicillin-resistant Staphylococcus aureus in intensive care units

Abstract: MRSA control in these ICUs characterized by a high prevalence of MRSA at admission was achieved via multiple factors, including screening, contact precautions, and use of alcoholic handrub solution. Our results after adjustment of risk factors for MRSA acquisition and the steady improvement in MRSA over several years strengthen these findings. MRSA spreading can be successfully controlled in ICUs with high colonization pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
9

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 36 publications
2
81
1
9
Order By: Relevance
“…Consistent with earlier reports on MRSA acquisition, we found that patients who acquired nosocomial MRSA were older, 28 had longer LOS, 15,17,29,30 and more frequent exposure to macrolides. 31 Interestingly, we found no statistical association with fluoroquinolones and cephalosporins, 13,14,17,32 but this is possibly related to a lack of power due to the low number of patients exposed to these antibiotics in our population.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with earlier reports on MRSA acquisition, we found that patients who acquired nosocomial MRSA were older, 28 had longer LOS, 15,17,29,30 and more frequent exposure to macrolides. 31 Interestingly, we found no statistical association with fluoroquinolones and cephalosporins, 13,14,17,32 but this is possibly related to a lack of power due to the low number of patients exposed to these antibiotics in our population.…”
Section: Discussionsupporting
confidence: 91%
“…This value reflects a more accurate estimate of incidence, as it accounts for length of stay in the ICU before the time of MRSA colonization, as opposed to including all ICU-days in the denominator. Others have used the total number of patient-days to calculate the incidence density of MRSA colonization, 31,32 which would underestimate the true acquisition rate.…”
Section: Discussionmentioning
confidence: 99%
“…[77][78][79][80][81][82] ii. Not all studies, however, have come to the same conclusion, 83,84 including the single cluster-randomized trial of targeted MRSA active surveillance where active surveillance and use of barrier precautions in ICU patients was not associated with a reduction in MRSA colonization or infection, although limitations in the study design and suboptimal use of barrier precautions prevent definitive conclusions from being drawn.…”
Section: Section 2: Background-strategies To Detect Mrsamentioning
confidence: 99%